Minimising embodied carbon in reinforced concrete beams. (1st September 2021) - Jayasinghe, Amila; Orr, John; Ibell, Tim; Boshoff, William P.
Highlights: Parametric design of prismatic concrete beams reduces embodied carbon by up to 38%. Further savings of up to 8% are possible with parametric shape optimisation. Optimum designs for a given span vary with design criteria. Estimating deflections alongside optimisation algorithm expands the design space. Abstract: The construction industry has received attention due to its significant contribution to global carbon emissions. In this paper, conventional design and construction practices of reinforced concrete beams are scrutinised to explore the potential for reductions in embodied carbon. For a given set of design criteria, a family of discrete beam designs which have different geometries and corresponding reinforcements were developed to identify those with minimum embodied carbon. Two algorithms for shape optimisation were developed, one to identify the geometry of the theoretical optimum design, and another considering technical and construction feasibility. Prismatic beams were also optimised exploring alternative designs with different depths and widths along with the required reinforcements, for a reasonable comparison. Several cases were studied to understand the effect of different design parameters. Different design criteria suggested different geometries to minimise embodied carbon, even if the design span was the same. The importance of minimising web width was seen throughout the analysis. The expected deflection of each design was also estimated to understand the effect of optimisation on serviceability performance and found to be satisfactory in all the cases. Embodied carbon of beams can be reduced by up to 38% by optimising prismatic beams compared with conventional designs. Further savings up to 8% are possible with a feasible shape optimised design compared with optimised prismatic beams.